Using Pictorial Exemplars in Two-Dimensional Design Education - Shaw, Jacque (Centre for Promoting Ideas, 2012)
This discussion paper describes the use of pictorial exemplars in two-dimensional (2D) design; how they help with learning and what factors or variables, such as positioning; deconstruction, explanation and guidance; discussion and feedback; motivation; and cultural aspects contribute to their success or failure. It also aims to highlight some of the discrepancies that exist between the perceptions of lecturers and students regarding the usage of exemplars. Discrepancies in opinion of the use exemplars between year groups were also noted. Lecturers and students from the Department of Design were interviewed for this discussion paper to provide the information on how pictorial exemplars are used by lecturers and received by students. It aimed to provide qualitative data on what were perceived as the positives as well as the negatives of using exemplars to explain design concepts. The word exemplar in this paper means a typical model from a particular genre of 2D design, for example packaging, advertisement, poster, corporate identity, etc., and is used interchangeably with the word example. Subjective qualities such as best, highest ideal or winner are not intended to be attached to the description of exemplar. Comments from experienced lecturers, design students and from referenced sources will be examined in this paper.